If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 11y = 52 Solving x + 11y = 52 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11y' to each side of the equation. x + 11y + -11y = 52 + -11y Combine like terms: 11y + -11y = 0 x + 0 = 52 + -11y x = 52 + -11y Simplifying x = 52 + -11y
| 32=7t-168 | | 6(x+3x)=6 | | 4u+2/2u | | 4u+1/2u | | 2c+12=10 | | 3t-15=4r | | 5x+6x^2-16/2x+3 | | x^2+361= | | -26+7x=4x+13 | | -14+x=x-4+2x | | -87+7x=-4x+100 | | 24-8x=-24 | | 3x+6x-2=1 | | -147-x=-10x+60 | | 14-k=-k-2k | | (2x-5)+(6x^2-6x-11)= | | -4+5a=4a-2 | | -147-x=-10x+50 | | x+8=-11+2x-6+4x | | 8x-55=45+3x | | 3u^3-6u^2= | | 2a+21=8a+9 | | -8x-55=45+3x | | 24o=(-36) | | (2x-5)(6x^2-6x-11)= | | -124+12x=4x+44 | | 4x+1=5x^2 | | 100-55x=3 | | 4x+1=x^2 | | -114+10x=-2x+138 | | 4=3t-5 | | -9x-29=-11x+9 |